A key discovery at the TiO2/dye/electrolyte interface: slow local charge compensation and a reversible electric field. Issue 26 (14th July 2015) - Yang, Wenxing; Pazoki, Meysam; Eriksson, Anna I. K.; Hao, Yan; Boschloo, Gerrit
<x xml:space="preserve">Abstract</x> Photo-induced absorption spectroscopy on dye-sensitized solar cells reveals reversible electron-induced cation adsorption at the TiO2 surface, resulting in changes of the surface electric field.